Comparing solution methods for dynamic equilibrium economies - S. Boragan Aruoba; Jesus Fernandez-Villaverde; Juan Francisco Rubio-Ramirez (Federal Reserve Bank of Atlanta, 2003)
This paper compares solution methods for dynamic equilibrium economies. The authors compute and simulate the stochastic neoclassical growth model with leisure choice using Undetermined Coefficients in levels and in logs, Finite Elements, Chebyshev Polynomials, Second and Fifth Order Perturbations and Value Function Iteration for several calibrations. The authors document the performance of the methods in terms of computing time, implementation complexity and accuracy and they present some conclusions about their preferred approaches based on the reported evidence.
Keywords: 330